Motivation and genre as social action: a phenomenological perspective on academic writing - Russell, David R. (Frontiers in Psychology, 2023)
This article discusses the relationship between motivation and genre in the context of academic writing, aiming to further bridge the gap between information-processing (IP) cognitive approaches and socio-cultural or dialogical approaches to understanding cognition. The author takes one significant recent article bridging the gap, Graham’s Writers Within Communities (WWC) model, as a starting point and attempts to add concepts from genre as social action and Deci and Ryan’s Self-Determination Theory (SDT). The article explores how genre as social action is intimately connected with motivation and how SDT’s principles of competence, autonomy, and relatedness align with the phenomenological perspective on genre and motivation. The author suggests that these theories provide a more comprehensive understanding of writing motivation, emphasizing that the perception of genre as social action is a crucial motivator for writers and that self-determination is vital to authentic self-regulation in academic writing. The article illustrates the uses of the additional theories with an interview-based case study of a dissertation writer. It ends by discussing the possible implications of this theoretical research for empirical research on student motivation from both IP cognitive and sociocultural perspectives.